2013
DOI: 10.5114/pg.2013.39922
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and postprandial levels of ghrelin, leptin and insulin in lean, obese and anorexic subjects

Abstract: IntroductionGhrelin, leptin and insulin are involved in neurohormonal regulation of energetic homeostasis.AimWe investigated the correlation between nutritional status and plasma levels of leptin, ghrelin and insulin in lean, obese and anorexic subjects.Material and methodsNineteen obese and 18 anorexic adults were enrolled in the study. Seventeen adults with normal body mass index (BMI) served as controls. Blood samples were taken twice: before breakfast and 2 h after breakfast. Fasting and postprandial ghrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
(29 reference statements)
6
29
3
Order By: Relevance
“…For normal weight individuals, one study showed that leptin decreased at 6 h [44] such as in our study, unchanged in other studies [18,19], whereas an increase was observed in other reports [20][21][22]. In obese individuals two reports showed a significant postprandial decrease in leptin [21,22], as well as no postprandial leptin changes were observed in other studies [18,19]. Finally, opposite to our observation of the secretion of adiponectin, no initial close to significant, increase of leptin was observed.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…For normal weight individuals, one study showed that leptin decreased at 6 h [44] such as in our study, unchanged in other studies [18,19], whereas an increase was observed in other reports [20][21][22]. In obese individuals two reports showed a significant postprandial decrease in leptin [21,22], as well as no postprandial leptin changes were observed in other studies [18,19]. Finally, opposite to our observation of the secretion of adiponectin, no initial close to significant, increase of leptin was observed.…”
Section: Discussioncontrasting
confidence: 77%
“…These results contradict for the most other reports. For normal weight individuals, one study showed that leptin decreased at 6 h [44] such as in our study, unchanged in other studies [18,19], whereas an increase was observed in other reports [20][21][22]. In obese individuals two reports showed a significant postprandial decrease in leptin [21,22], as well as no postprandial leptin changes were observed in other studies [18,19].…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Thus, high leptin and low ghrelin suppress the appetite, while low GLP-1 and glucagon contribute to appetite stimulation. The final effect on a child will also depend on meal content, the amount of high-fat and sugar, including fructose, the amount and distribution of body and liver fat content, the effects on insulin sensitivity and glucose metabolism, the basal nutritional status, gonadal status, exercise level, the integrity of the brain-gut axis, and their genetic susceptibility for diabetes mellitus (Bouret, 2013;Pettus et al, 2013;Korek et al, 2013;Shah and Vella, 2014;Liu et al, 2014aLiu et al, , 2014bLiu et al, , 2014cLaughlin,2014). Low levels of ghrelin are of concern in children given its involvement in the regulation of growth hormone, memory and learning, food addiction and neuroprotection (Albarran-Zeckler et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Insight into the modification of the endogenous ghrelin system seems to be promising not only for the control of obesity, but also for the management of clinically significant anorexia and pathological weight reduction. Accumulating evidence has shown that in patients with anorexia nervosa, there is a paradoxical increase in plasma ghrelin level even when compared with matched controls or obese patients (26), suggesting that there might be an insensitivity to ghrelin (27). Moreover, in vitro studies have documented that intra-peritoneal or systemic administration of ghrelin has the potential to improve the appetite and the nutritional status, and at the same time reduce the metabolic rate in patients with end-stage cancer (5).…”
Section: Ghrelin and Anorexiamentioning
confidence: 99%